Evaluation of Patient Exposure After an Emergency Warm-Up of the CT X-Ray Tube - Desislava Kostova-Lefterova; Desislava Ivanova; Filip Simeonov; Anna Zagorska; Kameliya Genova; Petya Ilieva (Journal of Biomedical & Clinical Research, 2020)
A survey was performed to evaluate patient exposure after a procedure for the CT X-ray tube’s emergency warm-up, with the patient positioned on the table within the CT gantry. Three CT units, situated in three different University hospitals, were included in the survey. The evaluation was performed with AGFA personal monitoring films to visualize the results and discuss them with the radiographers who operate the systems. Additional measurements were performed with the RaySafe X2 system to demonstrate the presence of exposure. The air kerma resulting from implementing the warm-up protocol was evaluated to be higher than 112 μGy, 409 μGy, and 807 μGy for each of the CT units. Those values were underestimated because of the dosimetry equipment used and the methodology. A discussion between medical staff, engineers, and medical physicist was initiated. The practice with unnecessary patient exposure was terminated.